Antidepressants vs. Placebo for the Treatment of Functional Gastrointestinal Disorders in Adults: A Systematic Review and Meta-Analysis - Xiong, Nana; Duan, Yanping; Wei, Jing; Mewes, Ricarda; Leonhart, Rainer (Frontiers in Psychiatry, 2018)
Objective: To integrate high-quality evidence of the efficacy of antidepressants across different subtypes of functional gastrointestinal disorders (FGIDs). Methods: The Medline, PsycINFO, EMBASE, the Cochrane Library, and Chinese local database were searched up to October 1, 2017. Keywords included all subtypes of FGIDs, antidepressants, and randomized controlled trials (RCTs). We included RCTs with low to moderate risks of bias in comparing antidepressants with placebos as the only intervention in treating adult patients with FGIDs (PROSPERO ID: CRD42015030123). Language was restricted to English or Chinese. Data extraction was independently carried out by two authors, following the Cochrane Handbook for systematic reviews. Results: Of 2,460 records identified, 31 studies reporting on 2,340 participants were included in the meta-analysis. Antidepressants were more effective than placebos in terms of the rate of responder [RR = 1.35 (95% CI 1.12 to 1.63)], reduction of symptoms [SMD = -0.94 (95% CI -1.33 to -0.54)], and disability severity (moderate effect sizes). Those effects partly remained both at the presence and absence of comorbid depression, and among different subtypes of FGIDs. Subgroup analyses confirmed the benefit of tricyclic and tetracyclic antidepressants, selective serotonin reuptake inhibitors (SSRIs), and trazodone. Efficacy of serotonin and norepinephrine reuptake inhibitors (SNRIs), low doses of antidepressants, and antidepressants in intermediate to long term treatment was inconclusive due to the scarcity of eligible evidence. Compared to placebo, patients on antidepressants reported more adverse events [RR=1.91 (95% CI 1.23 to 2.96)] and more frequent withdrawal. On average one in 7.4 (95% CI 5.4 to 11.9) patients treated with antidepressants responded, while one in 4.8 (95% CI 3.7 to 6.8) experienced certain adverse effects. Conclusions: Antidepressants were inferior to placebo in terms of tolerability and partly superior regarding efficacy. Before prescribing antidepressants, the benefits and side effects should be carefully evaluated.